Circular bioeconomy and sustainable food systems: what are the possible mechanisms? - Nguyen, Thi Hoa; Wang, Xinfang; Utomo, Dhanan; Gage, Ewan; Xu, Bing (Elsevier, 2025)
The circular bioeconomy has emerged as a promising pathway for sustainable development, yet its specific role in fostering sustainable food systems remains underexplored. To our best knowledge, this study is the first systematic review to examine how the circular bioeconomy contributes to sustainable food practices. Using content analysis of 111 academic papers from SCOPUS database, we identify key mechanisms through which the circular bioeconomy enhances food safety and security. These include the development of innovative food products manufactured from bio-resources, the extension of product life through utilizing biodegradable films and bio-based compounds, and the improvement of food safety via sustainable packaging. Additionally, circular bioeconomy practices increase agricultural productivity by enhancing crop yields. From a corporate perspective, they optimize resource use, boost profitability, and generate new revenue streams from waste. Socially, these practices improve stakeholder wellbeing and generate employment opportunities. Environmentally, they support natural capital regeneration, reduce ecological footprints, and promote the sustainable use of resources. Despite these benefits, significant research gaps remain, particularly regarding the cross-sectoral relationships and multi-level impacts of circular bioeconomy practices. This study provides actionable implications for policymakers, practitioners, and researchers, emphasizing regulatory development, strategic decision making, and future research on corporate-level impacts.
Keywords: 30 Agricultural, Veterinary and Food Sciences; 3006 Food Sciences